Applied LGBT Museology: a management experience at the Museu das Bandeiras (Cadernos de Sociomuseologia, 2021)
This article will present the actions involving the themes of gender and sexual dissent developed by the Museu das Bandeiras between 2018 and 2020. The referred museum, starts to prioritize such themes from a new management, where the referred author is the direct of the institution. Thus, for two years, strategic actions were intensified that aimed at making women and LGBT people visible. It is noteworthy that the Museum of Flags, is located in an inland city located 200 km from the capital. The City of Goiás is known for the poems of Cora Coralina, in addition to its title of historical heritage of humanity and well-preserved houses and churches. In this article, we will use the concept of LGBT Museology, aiming to present in practice the activities developed in this institution that can be worked on in other conventional museums. As a methodology, a mapping of the actions carried out and the museum plan of the Museu das Bandeiras was carried out, which was divided into three phases; a) institutionalization; b) training and research; c) Dissemination actions based on the demands of the local community. To this end, the actions could only be carried out with the collaboration of the team and the local community that supported and stimulated the development of this projectKeywords: LGBT museology; Flags Museum; Museological Management; Gender; Sexual Dissent